Frihedsretorik og totalitære tendenser. Sand oplysning og danskhed hos Grundtvig - Harbsmeier, Eberhard (Grundtvig-Studier, 2001)
Freedom rhetoric and totalitarian tendencies. True information and Danishness at Grundtvig By Eberhard Harbsmeier